All Days 1992
DOI: 10.2118/24596-ms
|View full text |Cite
|
Sign up to set email alerts
|

Slimhole Drilling Hydraulics

Abstract: Drilling in small diameters is not new : the mineral industry currently drills slim holes in hard rocks. In this context, the drill string rotates at high speed very close to the hole wall, which is in general of good stability.To transfer that drilling method to the oilfield and keeping high rotation speed and small annulus, many problems occur due to the sedimentary type of formations drilled, and hydraulics become crucial for following points of view : the lifting up of cuttings in the annulus (no ball i i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…In separate studies conducted at drilling sites in the North Sea (Charlez 1998;Isambourg 1999), the effects of drillpipe rotation were studied while circulating and rotating at various rates inside casing (without cuttings), and the results were analyzed in terms of changes in ECD as calculated from downhole pressure tool data. In an early study of slimhole applications, the effects of drillpipe rotation on changes in ECD on narrow-annuli wells in Gabon (Delwiche 1992) were measured. In all of these early studies, no attempt was made to model the results into a coherent calculation scheme.…”
Section: Previous Workmentioning
confidence: 99%
“…In separate studies conducted at drilling sites in the North Sea (Charlez 1998;Isambourg 1999), the effects of drillpipe rotation were studied while circulating and rotating at various rates inside casing (without cuttings), and the results were analyzed in terms of changes in ECD as calculated from downhole pressure tool data. In an early study of slimhole applications, the effects of drillpipe rotation on changes in ECD on narrow-annuli wells in Gabon (Delwiche 1992) were measured. In all of these early studies, no attempt was made to model the results into a coherent calculation scheme.…”
Section: Previous Workmentioning
confidence: 99%
“…hole, confirm field observations that high-speed pipe rotation increases as annular pressure drops. 6,8 Drilling-Ahead Model. The EKD dynamic model was required to run continuously for each bit run.…”
Section: The Hydraulic Modelmentioning
confidence: 99%
“…A simple pressure-drop calculation confirms that in slimhole the annulus will provide the bulk of pressure losses, a result confirmed by Bode et al 1 The annular pressure drop is also very sensitive to the rotational speed of the drillpipe. A number of authors 1,[5][6][7]9 have demonstrated the increase in annular pressures caused by drillpipe rotation at high speed. The additional pressure caused by pipe rotation is such that pressures and flowrates will be affected throughout the well.…”
Section: Introductionmentioning
confidence: 99%
“…Delwiche et al (1) and Marken et al. (2) investigated using real wells' pipe rotation effects on pressure loss and found that frictional pressure loss increased if rotation to the inner cylinder in the annulus was applied.…”
Section: Introductionmentioning
confidence: 99%